Քեսապի ուտելի հատապտղային վայրի բոյսերը - Չոլաքեան, Յակոբ (տպ. Atlas)
The paper focuses on the wild naturally growing edible plants of Kesab and divides them into two categories: a) forest-growing wild plants, b) those grown on cultivated lands and in gardens. Both are considered berra, a term in Kesab dialect that means wild. The author describes the features of each plant, its impact on health, its usage, and whether it can be inoculated and pruned aſter replanting. The author highlights the perceptions of the peasant regarding these plants and trees, as well as folk traditions related to some of these wild trees. The wild plants/trees the author discusses in this paper are: the fabaceae, anacardiaceae, anacardiaceae, ericaceae, asparagaceae, fagaceae, oleaceae, rosaceae, myrtaceae, crataegus azarolus, crataegus ovalis, wild prune, wild pears (like makheokh, hourgoumilina), and vitis. The author notes that some of these plants have totally local names, like the chakhchina, as it grew close to waters and next to mills (chakhch being the corrupted version of chaghatsk, mill).
Keywords: Հատապտուղներ; Քեսապ